Physics of nova outbursts: A theoretical model of classical nova outbursts with self-consistent wind mass loss. (18th July 2022) - Kato, Mariko; Saio, Hideyuki; Hachisu, Izumi
Abstract: We present a model for one cycle of a classical nova outburst based on a self-consistent wind mass loss accelerated by the gradient of radiation pressure, i.e., so-called optically thick winds. Evolution models are calculated by a Henyey code for a 1.0 M_ white dwarf with a mass-accretion rate of 5 × 10 −9 M_ yr −1 . The outermost part of the hydrogen-rich envelope is connected to a steadily moving envelope where optically thick winds occur. We confirm that no internal shock waves occur at thermonuclear runaway. The wind mass-loss rate reaches a peak of 1.4 × 10 −4 M_ yr −1 at the epoch of the maximum photospheric expansion, where the photospheric temperature decreases to log T ph (K) = 3.90. Almost all of the accreted mass is lost in the wind. The nuclear energy generated in hydrogen burning is lost in a form of photon emission (64%), gravitational energy (lifting up the wind matter against gravity, 35%), and the kinetic energy of the wind (0.23%). A classical nova should be very bright in a far-UV (100–300 Å) band for one day just after the onset of thermonuclear runaway (∼ 25 d before the optical maximum). In the decay phase of the nova outburst, the envelope structure is very close to that of a steady-state solution.